2021
DOI: 10.3390/met11122055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Step Austempering Treatment on the Microstructure and Mechanical Properties of a High Silicon Carbide-Free Bainitic Steel with Bimodal Bainite Distribution

Abstract: The effect of multi-step austempering treatments on the microstructure and mechanical properties of a novel medium carbon high silicon carbide-free bainitic steel was studied. Five different isothermal treatment processes were selected, including single-step isothermal treatments above martensite start temperature (at 350 °C and 370 °C, respectively), and three kinds of two-step routes (370 °C + 300 °C, 370 °C + 250 °C, and 350 °C + 250 °C). In comparison with single-step austempering treatment adopting a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…These are silicon-based steels (>1.5 wt.%) characterized by ultimate tensile strength values above 2000 MPa and elongation up to 20% [19,20]. These findings have thus served as inspiration for numerous studies that have led to the development of novel steel compositions with tailored properties, which have found applications in various industrial sectors thanks to the remarkable weight reduction of the structures [21][22][23][24][25][26][27][28]. For example, currently, tunnel boring machines, high-power generators, components for wind turbines [29], and diesel injector systems [29] are manufactured with nanostructured steels.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These are silicon-based steels (>1.5 wt.%) characterized by ultimate tensile strength values above 2000 MPa and elongation up to 20% [19,20]. These findings have thus served as inspiration for numerous studies that have led to the development of novel steel compositions with tailored properties, which have found applications in various industrial sectors thanks to the remarkable weight reduction of the structures [21][22][23][24][25][26][27][28]. For example, currently, tunnel boring machines, high-power generators, components for wind turbines [29], and diesel injector systems [29] are manufactured with nanostructured steels.…”
Section: Introductionmentioning
confidence: 94%
“…Ausforming accelerates the bainitic transformation since the deformations modify the activation energy for the bainitic ferrite formation, leading to stress-and strain-induced transformations that enhance the transformation kinetics [28,[33][34][35][36]. Additionally, double-step treatments [24,37] lead to the acceleration of the bainitic transformation by the formation of a first population of bainitic ferrite at high temperatures, where the reaction kinetic is generally faster compared to low-temperature transformation. Moreover, this provides nucleation sites for bainitic ferrite plates, which are refined since they formed at a low temperature, significantly reducing the incubation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of Franceschi M. et al [ 16 , 17 ] dealt with the influence of different or multi-stage tempering on the resulting mechanical and corrosion-resistant properties of bainitic steel. It is clear from their results that an increase in the austenitization temperature leads to an increase in the volume fraction of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
“…
Advanced high-strength steels (AHSS) are considered very attractive materials thanks to their outstanding strength combined with high ductility. [1][2][3][4] Several authors in the literature demonstrated their capability to achieve mechanical strength higher than 1.5 GPa with elongation above 15%. [5][6][7][8] This extremely favorable combination of mechanical properties makes these steel grades new leading actors in important industrial fields such as automotive (i.e., safe and lightweight components, which allow a strong reduction in oil consumption and CO 2 emission), railways application due to their high wear resistance in comparison with standard pearlitic steels, [2,[9][10][11][12] and armor.
…”
mentioning
confidence: 99%